Studies on Arylhydrazones, Part-XII: Action of Bromine on Ethylhydrogen Mesoxalate Phenylhydrazones - Prasad, N.; Sahay, A; Prasad, J.; Singh, K.R.K (Asian Journal of Chemistry, 2010)
The nature of brominated product is dependent on the amount of bromine and time of reaction in the bromination of ethylhydrogen mesoxalate phenylhydrazones (IV). The products are identified as (Z-) form. Bromination of (IV) further revealed that nuclear bromination first takes place, followed by displacement of COOH group and then again nuclear bromination. It seems that electron withdrawing groups in aromatic nucleus deactivates the ring to such an extent that bromination in the nucleus does not take place even with excess of bromine in the presence of sunlight and on increasing the temperature. On the other hand, electron releasing groups in the aromatic nucleus activate the ring and nuclear bromination occurs with excess of bromine in sunlight.